Gastrocnemius Neuromuscular Activation During Standing Explosive Acceleration - Ana Ferri-Caruana; Carlos Sendra-Pérez; Jose Ignacio Priego-Quesada (Life)
The gastrocnemius muscle plays a crucial role in transmitting and generating energy during standing explosive accelerations, and as a consequence, is a muscle with high injury prevalence, especially the medial gastrocnemius (MG). This study aimed to compare the neuromuscular activation of the lateral gastrocnemius (LG) and MG during one of the most common standing explosive accelerations performed in team sports—the false start that occurs in jumps where the leg steps back before moving forward. Forty-two physically active participants (34 males: age = 24 ± 5 years, body mass = 73 ± 10.4 kg; and 8 females: age = 26 ± 5 years, body mass = 57.1 ± 6.8 kg) underwent electromyography analysis of the MG and LG in the four first foot contacts of standing explosive acceleration. The results showed that the third contact differed significantly from others (LG vs. MG: 76.48 ± 3.10 vs. 66.91 ± 2.25, p = 0.01, ES = 0.5), with the LG exhibiting earlier activation and higher peak sEMG activity compared to the MG (LG vs. MG: 0.12 ± 0.01 vs. 0.13 ± 0.01, p = 0.02, ES = 0.4). Additionally, the MG displayed longer duration contractions in all the foot contacts except the third foot contact. In conclusion, the MG showed an earlier activation timing and a longer duration of contraction than the LG in the first foot contact. Additionally, the third foot contact showed a different pattern of neuromuscular activation between the MG and LG compared to the rest of the foot contacts.